PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT WASILE KABUPATEN HALMAHERA TIMUR - Nurkocim, Nurkocim; Nurlaila, Nurlaila (Jurnal MS, 2016)
The purpose of this studay was to determine and analyse how much influence and discipline of Â work to employee performance at at the distrect office wasile Halmahera district east of collection was Â done by distributing questionnaires, the analysis method used is multiple resgression analysis wit a Â sample of 33 responden. Statistic of test results showed that the t test(partial) control positive and significant effect on the performance (Y) employees at the district. (X1 ) employees and the district, t test (partial) discpine at the district office wasile eastrern Halmahera district, and thus of the test results F (simultaneously) showed that a significant difference between the independent variables namely the supervision and discipline of work on performance (Y) employees at the district office wasile Halmahera Timur district can be recelved.